2008
DOI: 10.1002/j.2161-1874.2008.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Counseling: Implications for Counseling Male Juvenile Sex Offenders

Abstract: Juvenile sex offenders (JSOs) often appear unmotivated to change, which thus necessitates a therapeutic approach that matches “resistant” client characteristics. In this article, the authors review common traits of JSOs, introduce motivational counseling as an effective treatment modality, and offer a case illustration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, Walters, Vader, Nguyen, Harris, and Eells (2010) suggested that person-centered approaches, such as MI, may be less appealing in the absence of more structured interventions that target problem behaviors. In other words, criminal justice trainees may seek additional active approaches to working with their clients, such as cognitive behavioral approaches (Patel, Lambie, & Glover, 2008). Hence, it is possible that trainees in criminal justice may approach learning MI with scepticism about how MI will work better than the current, more structured approaches to working with offenders.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Walters, Vader, Nguyen, Harris, and Eells (2010) suggested that person-centered approaches, such as MI, may be less appealing in the absence of more structured interventions that target problem behaviors. In other words, criminal justice trainees may seek additional active approaches to working with their clients, such as cognitive behavioral approaches (Patel, Lambie, & Glover, 2008). Hence, it is possible that trainees in criminal justice may approach learning MI with scepticism about how MI will work better than the current, more structured approaches to working with offenders.…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence is not as robust for offender populations and is specifically lacking for sex offender populations, it is reasonable to assume that common factors would be stable across populations absent evidence to the contrary. Although no direct prior studies were found that can be compared to the present one for purposes of replicating similar results, recent research in offender counseling has highlighted the importance of client-centered treatment (Calley & Gerber, 2008;Carrola, 2022;Carrola & Brown, 2018;Patel et al, 2008). More specifically, sex offender counselors have discussed the importance of relational factors (i.e., rapport, trust, and nonjudgmental acceptance) in achieving positive outcomes in sex offender counseling.…”
Section: Comparison With Prior Researchmentioning
confidence: 77%
“…The longstanding finding that the working alliance is positively associated with positive client outcomes in general counseling and psychotherapy has prompted scholars to identify counselor characteristics associated with forming strong working alliances and methods for fostering those characteristics (see Wampold & Imel, 2015). More recently, scholars have emphasized the importance of the therapeutic relationship in offender counseling (Calley & Gerber, 2008; Carrola, 2022; Patel et al., 2008) and have similarly found that the working alliance in offender counseling is also positively associated with client outcomes (Scanlon et al., 2022). Sex offender counselors may also benefit from knowing what counselor characteristics are associated with forming stronger working alliances in sex offender counseling, and methods for fostering those characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased public knowledge of sex offenders and their presence in the community, as well as the growth of responses to sex offenses, may be responsible for the development of treatment programs specifically designed for individuals convicted of sex offenses (Connor, Copes, & Tewksbury, 2012). Like sex offender registration, notification, and residency restrictions, the primary purpose of sex offender treatment is to increase public safety by preventing recidivism (Gerardin & Thibaut, 2004;Patel, Lambie, & Glover, 2008;Zgoba & Simon, 2005). Specifically, desistance from future sex crimes by previously convicted sex offenders is the desired end (Williams, 2009).…”
Section: Treatment As a Public Safety Toolmentioning
confidence: 99%